2016
DOI: 10.1590/0101-7438.2016.036.02.0321
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Artificial Neural Network and Support Vector Machine for Acute Coronary Syndrome Prognosis

Abstract: ABSTRACT. Despite medical advances, mortality due to acute coronary syndrome remains high. For this reason, it is important to identify the most critical factors for predicting the risk of death in patients hospitalized with this disease. To improve medical decisions, it is also helpful to construct models that enable us to represent how the main driving factors relate to patient outcomes. In this study, we compare the capability of Artificial Neural Network (ANN) and Support Vector Machine (SVM) models to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Findings in this study showed that the SVM algorithm performed better than other algorithms. [ 39 ] In a study, Akella examined six different data mining algorithms, including ANN and SVM algorithms for predicting CAD. The results showed that the ANN algorithm was better than other algorithms in all performance parameters, including accuracy, AUC, sensitivity, and F1-Score.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in this study showed that the SVM algorithm performed better than other algorithms. [ 39 ] In a study, Akella examined six different data mining algorithms, including ANN and SVM algorithms for predicting CAD. The results showed that the ANN algorithm was better than other algorithms in all performance parameters, including accuracy, AUC, sensitivity, and F1-Score.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil yang diperoleh adalah terpilihnya 6 dari 9 variabel dengan tingkat akurasi model prediksi menyamai model prediksi dengan 9 variabel input. Sementara pada [12] dilakukan modifikasi kriteria sensitivitas data berbasis jarak dengan menambahkan kriteria disagreement dimana perhitungan sensitivitas data hanya dilakukan pada data input yang memiliki output berbeda sehingga mengurangi kompleksitas komputasi. Metode seleksi variabel input yang digunakan mampu memilih 4 variabel signifikan dari kandidat 28 variabel input.…”
Section: Pendahuluanunclassified